Understanding the Synergistic Effect in Oxygen Evolution Reaction Catalysis from Chemical Kinetics Point of View: An Iron Oxide/Nickel Oxide Case Study. Issue 11 (21st July 2020) - Shit, Subhasis; Ghosh, Souvik; Bolar, Saikat; Murmu, Naresh Chandra; Kuila, Tapas
Abstract : The Oxygen Evolution reaction (OER) is still an enigmatic process, and a few research efforts have been deployed to understand its thermodynamic aspects. However, to date, no significant attention has been given to understand the chemical kinetics of the OER. Herein, the oxides of nickel and iron, and their heterostructure were chosen for the investigation. The electrocatalytic activity was found to augment synergistically when a heterostructure was formed between iron oxide and nickel oxide. The metal oxide catalyzed OER was an entropy-driven process and followed the peroxide linkage formation pathway. The rate-determining step was found to be different for the reactions catalyzed by different oxides. For the first time, Distribution of relaxation time (DRT) plots were utilized to study the chemical kinetics of OER, and the inference obtained from this analysis agreed well with the reaction mechanism. The kinetic barrier for the charge transfer process was found to decrease, and the surface group formation attained a moderate value after the heterostructure formation. These aspects had been the key player behind the synergistic increment in OER catalytic activity of the heterostructure. This investigation will lead a new pathway towards the development of strategies to understand the kinetics of an electrochemical reaction.